Economic Recovery in the Age of COVID-19 - Carlos Cuerpo (Intereconomics, 2022)
Economic recovery post-COVID-19 will be structured around answering a number of fundamental questions. It is necessary to take stock of the extent of the recovery and of the transformation our economies have experienced in the last year and a half.
Keywords: E62; 330; Wirtschaftskrise; Epidemie; Coronavirus; EU-Staaten